Targeting image-based autobiographical memory in childhood to prevent emotional disorders: Intervention development and a feasibility randomised controlled trial. (September 2021) - Pile, Victoria; Winstanley, Ali; Oliver, Abigail; Bennett, Eleanor; Lau, Jennifer Y.F.
Abstract: Maladaptive cognitive styles confer vulnerability for emotional disorders and may emerge in childhood. In three phases, we developed and evaluated a novel parent-led intervention (My Memory Forest) to target overgeneral memory and avoidance of negative memories. In phase 1, the intervention was co-designed using two focus groups (n = 30 children) and consultation with teachers and parents. The acceptability, feasibility, and clinical potential of My Memory Forest was initially evaluated in phase two (n = 12 children aged 6 to 9) and then in a feasibility randomised controlled trial in phase three, against an active control (n = 56 aged 6 to 9). Acceptability and engagement were good, and no harm was reported by parents or participants. Phase 2 identified decreases in self-reported anxiety (d = 1.08), depression (d = 0.51) and vividness of negative events (d = 0.53). There was little change in parent-reported symptoms. In phase 3, recruitment was highly feasible and participant retention excellent (100%) but parent retention poor (55%). Descriptive statistics indicated similar changes in anxiety and depression for both groups. Changes between Phases 2 and 3 (e.g. methods of recruitment) could explain the discrepancy between results. Further development is necessary before proceeding to another trial. Trial registration: ISRCTN13142918. Highlights: Imagery-based interventions could target problematic cognitive styles in childhood. My Memory Forest is a parent-led approach, co-designed with children and parents. It aims to ameliorate dysfunctional autobiographical memory processes. My Memory Forest is acceptable, feasible and safe to deliver in schools. Further development is required before proceeding to a definitive trial.